PENGARUH BRAND IMAGE, DISTRIBUSI, DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA PENGIRIMAN J&T EXPRESS DI DROP POINT KRAKATAU MEDAN - Darwin; Yayuk Yuliana (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2022)
This study aims to examine the effect of brand image (X1), distribution (X2), and promotion (X3) on consumer decisions (Y) to use J&T Express delivery services at Drop Point Krakatau Medan. The data used is data using probability sampling method, with a total sample of 98 respondents. The analysis method of this research uses multiple linear regression. The classical assumption test used has met the specified criteria, the t-test (partial test) shows that the brand image, distribution and promotion variables have a positive and significant effect on consumer decisions because the tcount > ttable brand image is 10.727 > 1.664, the tcount > ttable distribution of 2.698 > 1.664 and the value of tcount > ttable promotion of 11.872 > 1.664. From the results of the f test (simultaneous test) the value of fcount > ftable is 61,691 > 3.09, then this shows that brand image, distribution and promotion together have a significant effect on consumer decisions to use J&T Express delivery services at Drop Point Krakatau Medan.